2021
DOI: 10.1002/hep.31793
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Renal Outcomes Up to 96 Weeks After Tenofovir Alafenamide Switch From Tenofovir Disoproxil Fumarate in Routine Practice

Abstract: BaCKgRoUND aND aIMS: Real-world data for treatment effectiveness and renal outcomes in chronic hepatitis B (CHB) patients who were switched to the new and safer prodrug tenofovir alafenamide (TAF) from tenofovir disoproxil fumarate (TDF) are limited. Therefore, we aimed to evaluate treatment and renal outcomes of this population. appRoaCH aND ReSUltS:We analyzed 834 patients with CHB previously treated with TDF for ≥12 months who were switched to TAF in routine practice at 13 US and Asian centers for changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
60
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 23 publications
13
60
0
1
Order By: Relevance
“…TAF increased the ALT normalization rate according to the American Association for the Study of Liver Diseases (AASLD) criteria in the three randomized trials ( Lampertico et al, 2020 ; Agarwal et al, 2018 ). Recently, three retrospective studies in patients with CHB showed similar findings at 12 to 18 months after switching to TAF, but one study showed that the change was not significant at 6 months after switching to TAF ( Toyoda et al, 2021 ; Bernstein et al, 2021 ; Farag et al, 2021 ; Alghamdi et al, 2020 ). Our study showed that the decrease in ALT level persisted after switching to TAF, but the ALT normalization rate was similar at the time of switching and 48 weeks after switching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAF increased the ALT normalization rate according to the American Association for the Study of Liver Diseases (AASLD) criteria in the three randomized trials ( Lampertico et al, 2020 ; Agarwal et al, 2018 ). Recently, three retrospective studies in patients with CHB showed similar findings at 12 to 18 months after switching to TAF, but one study showed that the change was not significant at 6 months after switching to TAF ( Toyoda et al, 2021 ; Bernstein et al, 2021 ; Farag et al, 2021 ; Alghamdi et al, 2020 ). Our study showed that the decrease in ALT level persisted after switching to TAF, but the ALT normalization rate was similar at the time of switching and 48 weeks after switching.…”
Section: Discussionmentioning
confidence: 99%
“…TAF is a prodrug of tenofovir (TFV) that has less renal toxicity than TDF. The renal function of patients stabilized at 48 weeks after switching to TAF in a randomized trial and four retrospective studies ( Lampertico et al, 2020 ; Toyoda et al, 2021 ; Bernstein et al, 2021 ; Farag et al, 2021 ; Alghamdi et al, 2020 ). The renal outcome was similar in our study in that the median eGFR decreased during TDF therapy (100.09 vs 91.97 mL/min/1.73 m²) and stabilized at 48 weeks after switching to TAF (93.47 mL/min/1.73 m²).…”
Section: Discussionmentioning
confidence: 99%
“…The recent report also indicated that ALT normalization increased after switching from TDF to TAF. 27 This result seems to suggest that other factors contribute to the abnormality of ALT during TDF treatment, except This study had a few limitations. First, the treatment regimens before switching to TAF were heterogeneous.…”
Section: Discussionmentioning
confidence: 83%
“…In the Phase 3 TDF to TAF switch study, the proportion of patients with at least one CKD stage improvement was significantly higher in TAF‐treated patients compared with TDF‐treated patients (25% vs 8%, P < 0.0001), and the proportion of patients with at least one CKD stage worsening was significantly higher in TDF‐treated patients compared with TAF‐treated patients (14% vs 6%, P < 0.0001) 36 . In a retrospective analysis of switching, patients with reduced eGFR (<90 ml/min) at baseline had significant decreases in eGFR while on TDF, but not after TAF switch 51 . After Week 96 of switching to TAF, approximately one‐fifth of patients with mildly decreased eGFR (60–89 ml/min) improved to normal range, and approximately one‐third of patients with moderately decreased eGFR (below 60 ml/min) improved to eGFR 60–89 ml/min.…”
Section: Introductionmentioning
confidence: 94%
“…34 In other studies, evaluations of estimated glomerular filtration rate (eGFR) mostly showed improvements upon switching from TDF to TAF. 41,46,47,51 Not all TDF to TAF switching studies reported bone-related safety outcomes; however, those that did generally reported improvements (Table 2). 36,[39][40][41][42][43]47 In a prospective, single-arm study, BMD significantly increased from baseline to Week 24 in 75 patients switched from TDF to TAF.…”
Section: Renal and Bone Safetymentioning
confidence: 99%